Indian Tourism Industry and COVID-19: A Sustainable Recovery Framework in a Post-Pandemic Era - Pandey, Kshitija; Joshi, Sujata; Mahadevan, Kala (Vision, 2024)
The COVID-19 outbreak has impacted the global business environment and has resulted in significantly challenging multiple industries across the business spectrum. One of the industries facing severe adverse consequences is the travel and tourism industry. This study aims to assess and assimilate the overall impact posed by this pandemic to the Indian tourism industry and propose a sustainable recovery framework that would provide a guideline to all the Indian tourism industry stakeholders to forge the way forward in the post-pandemic era. The study adopts a narrative literature review-based approach to arrive at a sustainable recovery framework based on the analysis and evaluation of the literature on the proposed topic. The study finds that the Indian tourism industry has been significantly impacted by the ongoing pandemic and has altered the functioning of all the stakeholders in the industry.
Keywords: Indian Tourism; Sustainable Recovery Framework; Tourism Industry; COVID-19 Pandemic